2013
DOI: 10.1016/j.jmoldx.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X Screening by Quantification of FMRP in Dried Blood Spots by a Luminex Immunoassay

Abstract: Fragile X is the most common inherited cause of intellectual disability and is frequently associated with autism. The syndrome is due to mutations of the FMR1 gene that result in the absence of fragile X mental retardation protein (FMRP). We have developed a rapid, highly sensitive method for quantifying FMRP from dried blood spots and lymphocytes. This assay uses two new antibodies, a bacterially expressed abbreviated FMRP standard, and a Luminex platform to quantify FMRP. The assay readily distinguished betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 55 publications
8
80
0
Order By: Relevance
“…Together, their results provide further evidence that proteins involved in the FMRPmGluR5 signaling pathway are altered in Sch and mood disorders. These findings support the potential use of the qFMRP test for much broader clinical applications other than just fragile X disorders [19].…”
Section: Neurobiological Features and Targeted Treatments In Fragile supporting
confidence: 73%
See 1 more Smart Citation
“…Together, their results provide further evidence that proteins involved in the FMRPmGluR5 signaling pathway are altered in Sch and mood disorders. These findings support the potential use of the qFMRP test for much broader clinical applications other than just fragile X disorders [19].…”
Section: Neurobiological Features and Targeted Treatments In Fragile supporting
confidence: 73%
“…Furthermore, by quantifying FMRP (qFMRP) − the functional endpoint of FMR1 gene expression − a more comprehensive understanding of FXS biology may help improve the diagnosis, prognosis, and treatment options for affected individuals. To demonstrate the potential of the qFMRP assay, Asuragen recently collaborated with the LaFauci and colleagues [19], who methodologically advanced an effort in the field of using dried blood spots (DBS) aimed to reliably quantify FMRP [19]. It is noteworthy that after they screened 2000 individuals of all ages, they found that qFMRP test can identify PM females with low FMRP (methylated).…”
Section: Introductionmentioning
confidence: 99%
“…This variation has been demonstrated by ELISA technology but the technique is difficult to replicate in subsequent samples (155). Newer techniques including the immunoassay utilizing timeresolved Forster's resonance energy transfer (156) and also the Luminex immunoassay (157). These techniques will lead to a new understanding of FMRP deficits not only in FXSD, but also in other neurodevelopmental/ neuropsychiatric disorders.…”
Section: Resultsmentioning
confidence: 99%
“…These techniques will lead to a new understanding of FMRP deficits not only in FXSD, but also in other neurodevelopmental/ neuropsychiatric disorders. The recent publication of FMRP deficits in the brains of individuals with bipolar disorder, schizophrenia, depression and autism (156)(157)(158) has opened our eyes to the importance of FMRP outside of the FXSD population. Even more remarkable is the finding that the age of onset and overall IQ in those with schizophrenia is correlated with FMRP deficits in peripheral blood (159).…”
Section: Resultsmentioning
confidence: 99%
“…Another is the incorporation of an immunoassay which quantifies the amount of FMRP present in DBS samples, such as the method described by Reference [43].…”
Section: Discussionmentioning
confidence: 99%